2018
DOI: 10.5093/psed2018a1
|View full text |Cite
|
Sign up to set email alerts
|

Time Perspective, Coping Styles, Perceived Efficacy in Affect Regulation, and Creative Problem Solving in Adolescence and Youth

Abstract: The study evaluated, in a sample of 230 adolescents (147 males and 83 females, mean age = 16.67) and a sample of 181 young people (21 males and 160 females, mean age = 22.57), the relationships between time perspective and the following personal skills: coping styles, perceived efficacy on affect regulation, and creative divergent problem solving. Results highlight that future time perspective increases in value from adolescence to youth, while present time perspective decreases. Future time perspective is cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
2
7
0
2
Order By: Relevance
“…The result is consistent with the notion that FTP is a promoter of activities aimed at planning, as well as constructively dealing with the demands of the environment (Zimbardo and Boyd, 1999). Previous research suggested that it also facilitates creative problem solving (Zambianchi, 2018).…”
Section: Time Perspectives and Coping Stylessupporting
confidence: 88%
See 1 more Smart Citation
“…The result is consistent with the notion that FTP is a promoter of activities aimed at planning, as well as constructively dealing with the demands of the environment (Zimbardo and Boyd, 1999). Previous research suggested that it also facilitates creative problem solving (Zambianchi, 2018).…”
Section: Time Perspectives and Coping Stylessupporting
confidence: 88%
“…The hypothesized reason for this is the fact that time perspectives might affect primary and secondary appraisals (Anagnostopoulos and Griva, 2012). For instance, FTP can be associated to adaptive, engaged and flexible coping (Bolotova and Hachaturova, 2012;Zambianchi, 2018), PHTPto avoidant coping (Zambianchi, 2018) whereas PNTPto disengagement and maladaptive styles (Bolotova and Hachaturova, 2012).…”
Section: Time Perspectives and Copingmentioning
confidence: 99%
“…The results showed that time perspective had a direct and positive effect on academic self-efficacy and direct and negative effect on self-disability. This result in terms of time perspective effect on academic self-efficacy with the results of Taylor & Wilson (2019), Zambianchi (2018), Haghighi, et al (2018) and Omidian, et al (2015) and in terms of the effect of time perspective on disability were in line with the results of research by Golestaneh, et al (2016) and Omidian, et al (2015). Explaining these results based on the research of Golestaneh, et al (2016) can be said that time perspective is an essential dimension of the psychological structure of time that appears as a categorization of human cognitive processes experience in the context of past, present and future.…”
Section: Discussionsupporting
confidence: 88%
“…For example, the results of Taylor & Wilson (2019) showed that understanding time played an effective role in increasing self-efficacy. In another study, Zambianchi (2018) reported that time perspective had a positive and significant relationship with self-efficacy. Omidian et al (2015) in a study concluded that time perspective had a significant effect on self-efficacy and academic procrastination.…”
Section: Introductionmentioning
confidence: 95%
“…In Italy, a study conducted on emerging adults revealed that Future-oriented TP positively correlated with proactive coping, reflective, and preventive coping, whereas Present-oriented TP negatively correlated with reflective and preventive coping strategies (Zambianchi & Bitti, 2014). A follow-up study conducted on adolescents and young adults revealed that Present TP positively correlated with avoidant coping in both groups assessed (Zambianchi, 2018). Moreover, in the same study Future TP positively correlated with problem-solving coping in both samples, with social support coping in emerging adults, and negatively correlated with avoidant coping in emerging adults.…”
Section: Time Perspectives and Copingmentioning
confidence: 97%